2012
DOI: 10.1063/1.4754866
|View full text |Cite
|
Sign up to set email alerts
|

Small polaronic hole hopping mechanism and Maxwell-Wagner relaxation in NdFeO3

Abstract: In the modern micro-electronics, transition metal oxides due to their colossal values of dielectric permittivity possess huge potential for the development of capacitive energy storage devices. In the present work, the dielectric permittivity and the effects of temperature and frequency on the electrical transport properties of polycrystalline NdFeO3, prepared by solid state reaction method, are discussed. Room temperature Mossbauer spectrum confirms the phase purity, octahedral environment for Fe ion, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Therefore, polarization increases and hence the dielectric constant also increases. The decrease of dielectric constant at higher frequency can be explained on the basis of space charge polarization model of Maxwell [21] and is also in agreement with the Koop's phenomenological theory [22]. The decrease of dielectric constant at higher frequency can be explained on the basis that the solid is assumed as composed of well conducting grains separated by poorly conducting grain boundaries.…”
Section: Uniform Deformation Energy Density Model (Udedm):-supporting
confidence: 77%
“…Therefore, polarization increases and hence the dielectric constant also increases. The decrease of dielectric constant at higher frequency can be explained on the basis of space charge polarization model of Maxwell [21] and is also in agreement with the Koop's phenomenological theory [22]. The decrease of dielectric constant at higher frequency can be explained on the basis that the solid is assumed as composed of well conducting grains separated by poorly conducting grain boundaries.…”
Section: Uniform Deformation Energy Density Model (Udedm):-supporting
confidence: 77%
“…Pure composition possesses high dielectric constant even at room temperature, which is consistent with the dielectric reports of other orthoferrites. 18,19 This is due to the close-packing of oxygen ions having loosely bound electrons, as these electrons get distorted in an applied electric field. 19 On comparing the compositional variation of e 0 , it can be noticed that the magnitude of the dielectric constant as well as dispersion has increased in the x ¼ 0.1, 0.2, 0.3 samples as compared to the pure sample.…”
Section: Resultsmentioning
confidence: 99%
“…The exponent n has been found to behave in a variety of forms as a constant or decreasing and increasing with the temperature, but always varying within 0 < n < 1. 36 For NAO, the frequency dependence of conductivity does not follow the power law as given above but is well described by the double power law given as 43…”
Section: Conductivity Analysismentioning
confidence: 96%
“…The response of the grain boundaries, due to their higher resistance and capacitance, lies at the lower frequencies compared to the response of the grains. 36 It is observed that with the increase of temperature both grain and grain-boundary arcs shift to the higher frequency side. It is known that Z*-plots for polycrystalline dielectric materials do not always yield perfect semicircular arcs, they even become asymmetric.…”
Section: Impedance Formalismmentioning
confidence: 96%
See 1 more Smart Citation